History of Wills, Testators and Their Families in Late Medieval Krakow Tools of Power - Wysmułek, Jakub (Later Medieval Europe, 2021)
This volume offers the first comprehensive analysis of wills in late medieval Krakow. It presents the origins of testamentary acts in the Kingdom of Poland and its centre, Krakow, and their subsequent transformation from so called 'canonical wills' to 'communal wills'. Wysmułek discusses the socio-cultural role of wills and sets them in their contemporary legal, social, and economic context. In doing so, he uncovers their influence on property ownership and family relations in the city, as well as on the religious practices of the burghers. Ultimately, this work seeks to change the perception of wills by treating the testamentary act itself as an important agent of historical social change - a 'tool of power'. Readership: Urban historians of the late medieval period interested in the socio-cultural development of law, and anyone interested in medieval documentary history.